Synthesis of anisotropic silver nanostructures in presence of polyvinyl pyrrolidone (PVP): LSPR and SAXS analysis - Singh M.; Singh A.K.; Mandal R.K.; Sinha I. (My University, 2025)
We study polyvinyl pyrrolidone (PVP) stabilization of aqueous phase silver nanoparticles (AgNPs) sols. Glucose is used as the reducing agent. Addition of increasing amounts of NaOH cause interesting variations in sol pH and localized surface plasmon resonance (LSPR) behavior. The LSPR information is coupled with small angle X-ray scattering (SAXS) analysis and TEM imaging to delineate various nanoparticle characteristics. Both fractal aggregate nanostructures and anisotropic objects are found to form under different NaOH conditions. © 2011 Elsevier B.V.